Validating the social content management framework : a Delphi study - Wan Azlin Zurita Wan Ahmad,; Muriati Mukhtar,; Yazrina Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Today, organisations are resorting to social networks to engage with customers. These social media interactions result in social content, which, if well-managed, can lead to innovative improvements in the value offerings of the organisations. Thus, a proper social content management framework needs to be in place. However, there is a limited study in the concepts of social content and social content management. Based on literature review, this article articulates the components of the social content management framework and its building blocks based on the service science approach. The Delphi technique is used to validate the framework, which involved obtaining consensus among the experts by using a set of questionnaire. There are three components that are being validated, namely, factors that affect social content management, the definitions of social content and social content management, and the framework as a whole. It is hoped that the framework will be useful for researchers and practitioners in the field of social content management.